Târîhu Bağdâd ev Medîneti’s-selâm - 880-01 Hatîb el-Bağdâdî, 1002-1071. (Kahire)
14 cilt 7 ciltte (1. c. 441 sayfa, 2. c. 432 sayfa ; 3. c. 479 sayfa, 4. c. 476 sayfa ; 5. c. 511 sayfa, 6. c. 424 sayfa ; 7. c. 484 sayfa, 8. c. 524 sayfa ; 9. c. 512 sayfa, 10. c. 496 sayfa ; 11. c. 507 sayfa, 12. c. 524 sayfa ; 13. c. 512 sayfa, 14. c. 472 sayfa)